Usability assessment of a HOTS evaluation tool in Pancasila-based Citizenship Education - Agustina, Dewiyana; Sutini, Ai; Abidin, Yunus; Dewi, Dinie Anggraeni; Utami, Nissa Aulia Belistiana (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
The goal of this study is to use the System Usability Scale (SUS) method to see how useful a Higher Order Thinking Skills (HOTS) assessment tool would be in Pancasila Education. Thirty fifth-grade Pancasila Education teachers from primary schools took part in a quantitative descriptive method. We used SUS scores to determine how useful the developed tool was, using established usability standards to do so. The results show that the instrument got an average SUS score of 76.5, which puts it in the